Anti-Inflammatory Activity of β-thymosin Peptide Derived from Pacific Oyster (Crassostrea gigas) on NO and PGE2 Production by Down-Regulating NF-κB in LPS-Induced RAW264.7 Macrophage Cells - Dukhyun Hwang (Marine Drugs, 2019)
β-thymosin is known for having 43 amino acids, being water-soluble, having a light molecular weight and ubiquitous polypeptide. The biological activities of β-thymosin are diverse and include the promotion of wound healing, reduction of inflammation, differentiation of T cells and inhibition of apoptosis. Our previous studies showed that oyster β-thymosin originated from the mantle of the Pacific oyster, Crassostrea gigas and had antimicrobial activity. In this study, we investigated the anti-inflammatory effects of oyster β-thymosin in lipopolysaccharide (LPS)-induced RAW264.7 macrophage cells using human β-thymosin as a control. Oyster β-thymosin inhibited the nitric oxide (NO) production as much as human β-thymosin in LPS-induced RAW264.7 cells. It also showed that oyster β-thymosin suppressed the expression of prostaglandin E2 (PGE2), inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2). Moreover, oyster β-thymosin reduced inflammatory cytokines such as tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6). Oyster β-thymosin also suppressed the nuclear translocation of phosphorylated nuclear factor-κB (NF-κB) and degradation of inhibitory κB (IκB) in LPS-induced RAW264.7 cells. These results suggest that oyster β-thymosin, which is derived from the mantle of the Pacific oyster, has as much anti-inflammatory effects as human β-thymosin. Additionally, oyster β-thymosin suppressed NO production, PGE2 production and inflammatory cytokines expression via NF-κB in LPS-induced RAW264.7 cells.